Metabolomics reveals the role of acetyl-l-carnitine metabolism in γ-Fe2O3 NP-induced embryonic development toxicity via mitochondria damage. Issue 2 (7th February 2019) - Huang, Zhenyao; Xu, Bo; Huang, Xiaomin; Zhang, Yuqing; Yu, Mingming; Han, Xiumei; Song, Ling; Xia, Yankai; Zhou, Zhu; Wang, Xinru; Chen, Minjian; Lu, Chuncheng
Abstract: Iron oxides nanoparticles (FeO X NPs), including α-Fe2 O3, γ-Fe2 O3, and Fe3 O4, are employed in many technological applications. However, very few studies have investigated the embryonic developmental toxicity of FeO X NPs. In this study, metabolomics analysis were used to uncover the potential mechanisms of FeO X NPs developmental toxicity on embryo–larval zebrafish and mice. Our results indicated that γ-Fe2 O3 NP treatment could cause increased mortality, dropped hatching rate, etc., while α-Fe2 O3 and Fe3 O4 NPs showed no obvious effect. Through metabolomics analysis, a total of 42 metabolites were found to be significantly changed between the γ-Fe2 O3 NP-treated group and the control group ( p  < 0.05). Pathway enrichment analysis indicated the impairment of mitochondria function. γ-Fe2 O3 NP treatment caused abnormal mitochondrion structure and a decrease in mitochondrial membrane potential in zebrafish embryos. Meanwhile, ATP synthesis was decreased while oxidative stress levels were affected. It is noteworthy that acetyl-l -carnitine (ALCAR) ( p  = 6.79E − 04) andl -carnitine ( p  = 1.43E − 03) were identified with minimal p values, the relationship between the two counter-balance was regulated by acetyltransferase (crata). Subsequently, we performed rescue experiments with ALCAR on zebrafish embryos, and found that the mortality rates reduced and hatching rates raised significantly in the γ-Fe2 O3 NP-treated group. Additionally, γ-Fe2 O3 exposure could lead to increased absorbed fetus rate, decreased placental weight, lower expression of acetyltransferase (Crat), reduced ATP synthesis as well as increased oxidative stress ( p  < 0.05). Our findings demonstrated that γ-Fe2 O3 NP might affect the mitochondrial membrane potential and ATP synthesis by affecting the metabolism of ALCAR, thereby stimulating oxidative stress, cell apoptosis, and causing embryonic development toxicity.